Evaluasi dan Assesmen Pembiasaan Dzikir Pagi dalam Penguatan Nilai Spiritual Pada Anak Usia Dini di RA Ishlahul Ummah - Julaiha, Siti; Afia, Sariah; Rukayah, Ity (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to evaluate the implementation of morning dhikr at RA Ishlahul Ummah as a strategy to strengthen spiritual values in early childhood. Using a qualitative research method with a descriptive approach, data were collected through direct observation, interviews, and documentation of morning dhikr activities. The findings reveal that morning dhikr is conducted routinely after Dhuha prayers, with guidance involving teachers and students taking turns. This practice not only enhances children’s spiritual awareness but also instills Islamic values such as gratitude, discipline, and tranquility. However, several challenges were identified, including the tendency of young children to struggle with maintaining concentration for extended periods and the lack of parental support in reinforcing the dhikr habit at home. These challenges affect students’ ability to recite and understand the meaning of dhikr. The study recommends the use of creative media, parental involvement through regular evaluations, and varied approaches in fostering the dhikr habit to improve program effectiveness. The findings emphasize the importance of synergy between schools and parents in nurturing children's spiritual awareness from an early age. With consistent habituation and a supportive environment, morning dhikr significantly contributes to shaping Islamic character in children. The study’s recommendations can serve as a guideline for developing similar programs, both at RA Ishlahul Ummah and other educational institutions, to nurture a generation with strong spiritual values and noble character.